1995
DOI: 10.1111/j.1530-0277.1995.tb01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilatory State of Decompensated Cirrhosis: Relation to Hepatic Dysfunction, Ascites, and Vasoactive Substances

Abstract: The objective of this study was to determine the relations between the hallmark circulatory finding of decompensated cirrhosis, a reduced systemic vascular resistance (SVR), and the indices of hepatic decompensation, the accumulation of ascites, and the concentrations of various vasoactive substances. At a university-affiliated teaching hospital, eighteen hospitalized patients with cirrhosis and 18 age- and sex-matched healthy subjects were used. This was a case-control study. Measurements included cardiac dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Cardiac dysfunction may become manifest under strain or treatment with vasoconstrictors such as angiotensin II which normalize the afterload and left atrial pressure, as mentioned earlier (53,83,97,101). In the presence of hyperdynamic circulation, the blood volume is expanded and may increase venous return, cardiac preload, thereby leading to the persistent increase in CO which may result in prolonged strain of the heart, with impaired cardiac contractility as the outcome (33,64,66). Infusion of dextran in one human study and one with experimental cirrhosis has revealed a limited cardiac preload reserve with reduced ability to modulate cardiac performance under different loading conditions (53,102), but this aspect needs further investigation.…”
Section: The Cirrhotic Heartmentioning
confidence: 98%
See 2 more Smart Citations
“…Cardiac dysfunction may become manifest under strain or treatment with vasoconstrictors such as angiotensin II which normalize the afterload and left atrial pressure, as mentioned earlier (53,83,97,101). In the presence of hyperdynamic circulation, the blood volume is expanded and may increase venous return, cardiac preload, thereby leading to the persistent increase in CO which may result in prolonged strain of the heart, with impaired cardiac contractility as the outcome (33,64,66). Infusion of dextran in one human study and one with experimental cirrhosis has revealed a limited cardiac preload reserve with reduced ability to modulate cardiac performance under different loading conditions (53,102), but this aspect needs further investigation.…”
Section: The Cirrhotic Heartmentioning
confidence: 98%
“…Relations of the left ventricular end-diastolic volume to sodium excretion and to the cardiac effects of TIPS also point to an association between regulation of systemic haemodynamics, cardiac volumes and uid retention in cirrhosis. In most clinical studies, the mass of the heart has been found within the normal range (53,64), but some authors have reported increased left ventricular mass (66,67). Recently, in an experimental study of portal hypertensive rats, Perello et al found left excentric hypertrophy that correlated with the degree of hyperdynamic circulation (68).…”
Section: The Cirrhotic Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Although determinations of heart volumes in cirrhosis have shown somewhat divergent results, findings of relatively increased volumes support the assumption of impaired loading of the heart. Thus, both normal heart volumes, and increased left atrial and left ventricular end-diastolic volumes have been reported in cirrhosis (27,101,(105)(106)(107)(108). Møller et al (109) used a magnetic resonance imaging technique and showed that the right ventricular systolic and diastolic volumes decreased, and that the left ventricular systolic and diastolic volumes slightly increased.…”
Section: Systemic Circulation In Cirrhosismentioning
confidence: 99%
“…It has thus been shown that end-diastolic left ventricular pressure increases, and PAP, stroke index and left ventricular ejection fraction fall during exercise, indicating an abnormal ventricular response to stress (54,71,82). The reduced left ventricular afterload may mask a left ventricular dysfunction which only becomes manifest under strain of the myocardial function (66). On increasing the systemic vascular resistance by 30% to normal values with infusion of angiotensin in alcoholic cirrhotic patients, Limas et al reported that PCWP increased twice, which indicates that normalization of the afterload induces a left ventricular failure (83).…”
Section: The Cirrhotic Heartmentioning
confidence: 99%